Equity, Teaching Practice and the Curriculum Exploring Differences in Access to Knowledge - Wahlström, Ninni (Routledge Research in Education, 2022)
This book explores how different classroom discourses and concepts of knowledge permeate teaching in high- and low-performance classrooms. Drawing on empirical research from classrooms in Sweden, it presents a theory-based framework for classroom research. The book examines the central concepts of knowledge, curriculum, pedagogy and equity to discuss differences in access to knowledge and the implications of these differences for students' future opportunities and wellbeing. It analyses the relationships between different teaching factors and discusses teaching from democratic perspectives developed within curriculum theory. Combining insights from curriculum theory with insights from sociolinguistic and sociocultural classroom research, this project breaks new ground in how knowledge from curriculum content is recontextualised into concrete teaching practices in the context of a standards-based curriculum. Providing valuable insights into the intersections between classroom practice, student performance and teacher expectations, this book will be of great interest to academics, researchers and post-graduate students in the fields of curriculum research, education policy, teacher education and classroom practice.